Interrelationships among managerial incentives, leverage, dividend and performance of public listed companies in Malaysia - Ghasemi, Maziar (2016)
Little work has been undertaken with regard to how the Agency Theory could be used to explain the simultaneous interrelation among internal solutions for agency problems. In addition, no general consensus has emerged after many years of investigation, only inconsistent findings from empirical evidence are gained. In the case of Malaysia, capital structure is formed by the highest belonging of family businesses government properties, and managerial ownership. Moreover, it is also argued that capital structure is very much dependent on the dominant nature of the ownership structure in the Malaysian context, and also personal tax exemption causes Malaysian shareholders to pressure managers into receiving more dividends. In addition, managerial ownership shows uncertainty in regard to managers' remuneration in Malaysian firms. This study tries to shed the research gap through investigating the interrelation of managerial incentives with dividend, leverage, firm profitability in the light of agency problems within a firm. Three models are designed to fulfill these objectives by studying the simultaneous interrelation between (i) managerial incentives and leverage ;(ii) managerial incentives and dividend; and also (iii) investigating the synchronized interrelation between managerial incentives and firm profitability. This study examines 267 companies listed in the Main market of Bursa Malaysia during a nine-year period from 2005 to 2013. To solve these three models, some different econometrics methods are used, namely, 2SLS, 3SLS, 3SLS-CMP, and OLS. The empirical outcomes of all three models show positive two-way causal relationships between managerial ownership and managerial remuneration, indicating that not only managerial ownership has a positive effect on managerial remuneration, but also managerial remuneration has a positive impact on managerial ownership as well. Moreover, Model one also reveals a negative one-way causal effect of managerial ownership on leverage, and also a positive effect of managerial remuneration on leverage. However, leverage has no significant effect on managerial incentives. In addition, the findings of the second model indicate that higher ownership levels by executives, simultaneously, lead to higher amounts paid in dividend by Malaysian listed firms, although the payout policy that follow higher dividend leads to a decrease in the level of ownership by managers. In addition, managers who paid more dividends are encouraged with more compensation by shareholders; however, the change in managerial remuneration has no immediate impact on dividend decision. Furthermore, Model three reveals the reverse interrelation between managerial ownership and performance. It means, when the firm generates a higher level of profit compared to the past performance, the level of managerial ownership will increase. However, the increase of the shares by managers, generally, leads to a decline in the firm profitability. The findings also show that there is no simultaneous interrelation between managerial remuneration and firm profitability in the main market of Bursa Malaysia. This study has used empirical findings to show that the current corporate governance policies are not making the anticipated impacts on connecting performance and managerial incentives, and also not considering the full linkages between managerial incentives and financial internal controlling instruments. The theoretical arguments for this justification suggest the need for policy reviews which will enable shareholders and managers to mitigate the agency conflicts.